Daily Life - Ross, Stewart (Wayland Hove, 1999)
Examines the history, people, city-states, government, social structure, home and school life, clothing, meals, sports and games, religion, and daily activities of ancient Greece.
Include Color Illustration and Index
Keywords: Greece -- Civilization -- Manners and customs